Caffeine as A Natural Corrosion Inhibitor for Mild Steel in Nacl Solution - L.P. Xuan; M.A. Anwar; T. Kurniawan; H. M. Ayu; R. Daud; Y. P. Asmara (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2019)
Corrosion inhibitors are substances that added to the environment in small concentration and can effectively reduce the corrosion rate that of a metal surface. Natural inhibitors are one types of inhibitor being researched as it brings less environmental impact on the environment. This research was focused on the application of caffeine as inhibitor for corrosion of mild steel in seawater condition. The objective of this project was to develop the relationship between caffeine concentration on the corrosion of mild carbon steel in both static and moving solution contained 3.5-wt% NaCl. Three types of solution were prepared, which are NaCl without addition of caffeine, NaCl with 1-wt% of caffeine and NaCl with 2-wt% of caffeine. Corrosion testing was carried out by weight loss measurement. The microstructures of corroded mild steel specimens were observed under optical microscope. The experimental results indicated that by adding caffeine into the environment medium, weight loss of mild steel specimen was reduced. The corrosion rate of specimens was decreased when more caffeine was added to the environment. From optical microscopic observation, caffeine performed its inhibition effect likely by forming a protective layer which acts as barrier to prevent further corrosion of mild steel in NaCl solution.